The potential of dadih in increasing iron intake and its effect on Ret-He and sTfR in adolescent girls - Annisa Furkaniaty; Edward Kurnia Setiawan Limijadi; Anang Mohamad Legowo; Ahmad Syauqy; Gemala Anjani (Poltekkes Kemenkes Yogyakarta, 2023)
Background : Dadih is a fermented milk product that contains probiotics. Probiotics can increase the bioavailability of iron so that it can help in the effort to prevent iron deficiency anemia, especially in adolescent girls. Laboratory examinations that can be done to diagnose iron deficiency anemia include reticulocyte hemoglobin equivalent (Ret-He) and soluble transferrin receptor (sTfR). Objective : This study aims to determine the effect of dadih feeding on ret-he and sTfR levels. Method : This study used a randomized pre-posttest controlled group design with 40 healthy adolescent girls aged 12-15 years who were divided into 2 groups, control (KK) and intervention (KI). The participants received dadih and a placebo as much as 100 grams with a frequency of once a day. The study was conducted for 14 days. Statistical analysis using the Wilcoxon Test, Paired T-Test, and Mann-Whitney. Result : The results showed an increase in iron and protein intake after being given dadih. Ret-He level after being given dadih decreased but there was no significant difference (p = 0.088), while sTfR level increased and there was no significant difference (p = 0.322). There was no significant difference in Ret-He and sTfR levels before and after the intervention between KK and KI (p>0.05). Conclusion : Giving dadih alone for 14 days with a frequency of once a day can increase iron and protein intake but has not had a significant effect on Ret-He and sTfR levels in healthy adolescent girl.